2006
DOI: 10.1111/j.1365-2109.2006.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage conditions on viability of quiescent copepod eggs (Acartia tonsa Dana): effects of temperature, salinity and anoxia

Abstract: Copepods have proven to be an ideal source of live food for the production of marine fish larvae in aquaculture. Therefore, there is a need to develop new methods for production and storage of copepod eggs that can be hatched and used at fish farms. In the present study quiescent eggs of Acartia tonsa were stored for periods up to 35 weeks at different temperatures, salinities and oxygen conditions in a full factorial experiment. None of these storage conditions seemed to induce diapause in eggs even though th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 24 publications
(38 reference statements)
3
48
3
Order By: Relevance
“…Taken together, these results suggest that A. tonsa is expected to produce resting eggs during unfavourable feeding conditions during short day lengths and at relatively cold (\12°C) temperatures. Furthermore, Holmstrup et al (2006) reported subitaneous eggs from A. tonsa at the Limfjord to enter quiescence when incubated in anoxia and cold temperatures.…”
Section: Key Directive Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results suggest that A. tonsa is expected to produce resting eggs during unfavourable feeding conditions during short day lengths and at relatively cold (\12°C) temperatures. Furthermore, Holmstrup et al (2006) reported subitaneous eggs from A. tonsa at the Limfjord to enter quiescence when incubated in anoxia and cold temperatures.…”
Section: Key Directive Factorsmentioning
confidence: 99%
“…Using short-term (24 h) incubations at different salinities, they reported that changes in salinity affected egg volume but that the embryo was able to maintain its volume and osmolality as it is protected by an impermeable plasma membrane. Utilizing longer-term incubations, Holmstrup et al (2006) observed that A. tonsa eggs were viable for up to 20 weeks at salinities between 10 and 50 psu, but very low salinities were only tolerated for a short time. Katajisto (2006, study site: Northern Baltic Sea) found that the development of A. bifilosa eggs was not affected by darkness and low temperature but that eggs became quiescent under anoxic conditions.…”
Section: Key Directive Factorsmentioning
confidence: 99%
“…Production of Acartia tonsa continues to be refined . Recent success with the long-term cold storage of A. tonsa eggs could prove to be a valuable egg banking method Holmstrup et al, 2006;Drillet et al, 2007). Several small paracalanid species have also recently shown promise for mass scale culture (McKinnon et al, 2003;Shields et al, 2005;Vanderlugt and Lenz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have manipulated the salinity of the water containing eggs of A. tonsa and shown eggs can survive (Holmstrup et al, 2006;Højgaard et al, 2008). Højgaard et al (2008) had success inducing quiescence in eggs after an abrupt salinity change and high viability was achieved at salinities from 5 and 30 g/L, with low viability at 0 g/L.…”
Section: Discussionmentioning
confidence: 99%
“…Peck and Holste (2006) reported that the viability of A. tonsa subitaneous eggs stored at 4°C decreased linearly by 4% for every 20 days of storage. Holmstrup et al (2006) evaluated effects of temperature, salinity, and anoxia on survival of A. tonsa quiescent eggs following cold storage. The best results were obtained when the temperature was below 5°C, salinity was between 10-20 g/L, and there was no oxygen added to capped vials.…”
Section: Introductionmentioning
confidence: 99%